2014
DOI: 10.1007/s11120-014-9984-9
|View full text |Cite
|
Sign up to set email alerts
|

Strong shift from HCO3 − to CO2 uptake in Emiliania huxleyi with acidification: new approach unravels acclimation versus short-term pH effects

Abstract: Effects of ocean acidification on Emiliania huxleyi strain RCC 1216 (calcifying, diploid life-cycle stage) and RCC 1217 (non-calcifying, haploid life-cycle stage) were investigated by measuring growth, elemental composition, and production rates under different pCO2 levels (380 and 950 μatm). In these differently acclimated cells, the photosynthetic carbon source was assessed by a 14C disequilibrium assay, conducted over a range of ecologically relevant pH values (7.9–8.7). In agreement with previous studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 56 publications
8
49
1
Order By: Relevance
“…Cell division rates at pre-industrial DIC levels (∼ 2 mmol kg −1 ) are similar to those found in the published literature (Langer et al, 2006(Langer et al, , 2009Rickaby et al, 2010;Bach et al, 2013;Candelier et al, 2013;Hermoso et al, 2014;Kottmeier et al, 2014;Sett et al, 2014). Emiliania huxleyi is the fastest grower for the smaller cell size, achieving about one division per day (µ ∼ 0.7 day −1 ) ( Fig.…”
Section: Growth Rates and Coccosphere Sizessupporting
confidence: 86%
“…Cell division rates at pre-industrial DIC levels (∼ 2 mmol kg −1 ) are similar to those found in the published literature (Langer et al, 2006(Langer et al, , 2009Rickaby et al, 2010;Bach et al, 2013;Candelier et al, 2013;Hermoso et al, 2014;Kottmeier et al, 2014;Sett et al, 2014). Emiliania huxleyi is the fastest grower for the smaller cell size, achieving about one division per day (µ ∼ 0.7 day −1 ) ( Fig.…”
Section: Growth Rates and Coccosphere Sizessupporting
confidence: 86%
“…Coccolith malformation and dissolution occurs when pH is lowered in culture experiments (Bach et al, 2012;Kottmeier et al, 2014), and our results are the first evidence of this effect in natural coccolithophore assemblages. The fall in coccolithophore diversity and cell concentration pattern as CO 2 levels increased is not explained by dissolution of the assemblage at the seep.…”
Section: Discussionsupporting
confidence: 53%
“…A previous mesocosm experiment identified decreased net specific growth rate from 0.5 to 0.43 day À1 in the highest pCO 2 mesocosms, [72] and the reduced haptophyte equivalent Chl-a concentrations and calcified E. huxleyi abundance values seen in our medium and high pCO 2 mesocosms support this. However, in the laboratory, varying responses have been identified for different E. huxleyi strains where growth rates either increased, [9,70,73] remained unchanged as in this study [65,69,74] or decreased. [66,75,76] Specific growth rates during the E. huxleyi RCC1229 experiment were lower (0.48 day À1 for the 900 matm pCO 2 treatment and 0.47 day À1 for the ambient CO 2 control) than found previously for that strain under near-identical growth conditions at the same …”
Section: Community Development and E Huxleyi Growthmentioning
confidence: 57%